Standard Operating Procedures for harvesting and harvest evaluation in cassava - Akpotuzor, P.; Iluebbey, P.; Ayankanmi, T.; Oke, E.; Olaniyo, E.; Ogunpaimo, K.; Andrew, S. (International Institute of Tropical Agriculture, 2024)
In cassava breeding, harvesting is carried out to determine the root yield and assess other important traits. It marks the end of the fieldwork for an experimental cassava trial. Cassava field trials should be ready for harvesting 9-12 months after planting. Harvesting is done manually by a team composed of supervisors, technicians, and daily rated staff.